Pulmonary Artery Thrombosis in a Newborn With Severe Coronavirus Disease 2019. Issue 6 (10th May 2021) - Schulze-Schiappacasse, Clara; Alarcón-Andrade, Gonzalo; Valenzuela, Gonzalo; Ferreiro, Myriam; Cavagnaro, Agustín; García-Salum, Tamara; Gutiérrez, Monserrat; Medina, Rafael A.
Abstract : Supplemental Digital Content is available in the text.